2020
DOI: 10.1175/jcli-d-19-0181.1
|View full text |Cite
|
Sign up to set email alerts
|

The Building Blocks of Northern Hemisphere Wintertime Stationary Waves

Abstract: An intermediate-complexity moist general circulation model is used to investigate the forcing of stationary waves in the Northern Hemisphere boreal winter by land–sea contrast, horizontal heat fluxes in the ocean, and topography. The additivity of the response to these building blocks is investigated. In the Pacific sector, the stationary wave pattern is not simply the linear additive sum of the response to each forcing. In fact, over the northeast Pacific and western North America, the sum of the responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 63 publications
4
98
0
Order By: Relevance
“…0 south of ;508N. Such precursors have been found in observations (e.g., Black and McDaniel 2004;Cohen and Jones 2011;Garfinkel et al 2010) although their representation in models are generally model dependent (Gerber et al 2010). The vertical tripole of tropical wind anomalies represent the winds of the quasi-biennial oscillation, and in particular, with easterlies in the lower-middle stratosphere, provide favorable conditions for SSWs to occur (Holton and Tan 1980).…”
Section: A Zonal Wind Nam and Temperature Evolutionmentioning
confidence: 86%
See 4 more Smart Citations
“…0 south of ;508N. Such precursors have been found in observations (e.g., Black and McDaniel 2004;Cohen and Jones 2011;Garfinkel et al 2010) although their representation in models are generally model dependent (Gerber et al 2010). The vertical tripole of tropical wind anomalies represent the winds of the quasi-biennial oscillation, and in particular, with easterlies in the lower-middle stratosphere, provide favorable conditions for SSWs to occur (Holton and Tan 1980).…”
Section: A Zonal Wind Nam and Temperature Evolutionmentioning
confidence: 86%
“…(e.g., Matsuno 1970) where q u is the meridional gradient of quasigeostrophic potential vorticity (PV), N 2 is the static stability, k is the zonal wavenumber, c is the phase speed, H is the density scale height, and all remaining variables are as in earlier equations. Even though strictly speaking, the refractive index can only predict wave behavior in the Wentzel-Kramers-Brillouin (WKB) limit, many previous studies have shown that the refractive index can provide useful information despite the fact that their experiments may not satisfy the underlying assumptions (e.g., Chen and Robinson 1992;Simpson et al 2009;Garfinkel et al 2012). It is expected in this framework that waves tend to preferentially propagate away from regions of small n 2 toward regions of larger n 2 .…”
Section: Waveguide Evolutionmentioning
confidence: 99%
See 3 more Smart Citations